MYKOLA MUSHYNKA AND UKRAINIAN MUSICAL CULTU - Karas, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article focuses on the role of the famous scientist Mykola Mushynka (Slovakia) in the development of Ukrainian musical culture. The following main research objectives are being solved: to determine the line of Mushynka’s activity in the field of the development of Ukrainian musical culture; to outline the scientist’s main achievements in the field and their significance for Ukrainian culture.